Profiling of the published scientific research articles on Paedodontics, endodontics, dental restorative materials and direct restorative dentistry in SADJ over a period of ten years (2008 - 2018) - Gwengu, Pumela Rocky-Queen; Phalwane, Motlalepula Grace; Seeletse, Solly Matshonisa (Edelweiss Applied Science and Technology, 2026)
The study explored the dynamics of published scientific research articles on Paedodontics, endodontics, dental restorative materials and direct restorative dentistry in South African Dental Journal (SADJ) over a period of ten years (2008 - 2018). A descriptive study design was conducted by reviewing published Paedodontics, endodontics, dental restorative materials and direct restorative dentistry articles in SADJ. A total of 100 journals were reviewed. A total number of 197 research articles were published in the SADJ between the years 2008 and 2018 according to the field of expertise (Paedodontics, endodontics, dental restorative materials and direct restorative dentistry). For the 11-year period, a total of 59 (30%) articles in Endodontics, 51 (26%) in direct restorative material, 48 (24%) in direct restorative dentistry, with Paedodontics having the least number at 39 (20%) published in the SADJ. It was observed that all the publications in SADJ (according to field of expertise) showed a palpable diminishing trend between 2008 and 2018. In particular, the number of articles in Paedodontics decreased significantly from a peak of 13 recorded in 2008 to nil in 2016.